Integripelta acanthus n. sp. (Bryozoa: Eurystomellidae) — a tropical prey species of Okenia hiroi (Nudibranchia) - Gordon, D. P.; Rudman, W. B. (Zootaxa, 2006)
Integripelta acanthus n. sp., the first known tropical species of Eurystomellidae (Bryozoa, Cheilostomata), is described from Hong Kong. It differs from all other species of the family in that most zooids in the zone of astogenetic repetition bear thorn-like spines. The species is preyed upon by the specialist-feeding nudibranch Okenia hiroi.